Social policies during conservative governments. Santa Fe, 1937-1943 (Papeles, 2023)
The article constitutes an approximation to the context where the social policies were implemented in the province of Santa Fe in the late thirties and early forties. We consider an analysis of this type appropriate because the creation of the School of Social Service (ESS) in the city of Santa Fe was due, in other aspects, to the need to have qualified personnel to attend different social problems that gave rise to a state action with its own characteristics. In other words, we try to retrace the development process of social policies created by the provincial State, a context where the creation of the ESS can be interpreted as an emergent. We focus specifically on health and housing policies during these years when the conservative governments attended to them from a perspective in which they could not be separated from the rest.
Keywords: Social policies; health; housing; conservative governments; School of Social Service